No Time to Spare: Thinking about What Matters - Cart, Michael (The Booklist (Chicago, Ill. 1969), 2017)
The word blog, Le Guin writes, "sounds like a sodden tree trunk in a bog or maybe an obstruction in the nasal passage." Written from 2010 through 2015, her blogs address a variety of subjects loosely arranged in four parts that range from meditations on old age (Le Guin is now well into her eighties) to those she calls "Rewards," a section that includes one of the best entries in the book: her contemplation of a lynx she discovers in a museum.